2019
DOI: 10.1021/acsaem.9b01419
|View full text |Cite
|
Sign up to set email alerts
|

Perylenedianhydride-Based Polyimides as Organic Cathodes for Rechargeable Lithium and Sodium Batteries

Abstract: Organic carbonyl molecules have recently been investigated as redox-active electrode materials in rechargeable organic batteries (ROBs), and although redox-active polymers offer high specific energy density and tunable redox potential windows, their undesirable dissolution into aprotic electrolytes during charge/discharge cycling and their poor electronic conductivity compromised their utilization in ROBs. To overcome these challenges, we synthesized, for the first time, two 3,4:9,10-perylenetetracarboxylic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…The new vibrational peaks detected at 712 and 713 cm –1 are assigned to imide CO symmetric in-plane bending of BA-PI and PI, respectively. These result indicated that the complete conversion of the anhydride groups into the imide functionality in both BA-PI and PI during polymerization reaction …”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…The new vibrational peaks detected at 712 and 713 cm –1 are assigned to imide CO symmetric in-plane bending of BA-PI and PI, respectively. These result indicated that the complete conversion of the anhydride groups into the imide functionality in both BA-PI and PI during polymerization reaction …”
Section: Resultsmentioning
confidence: 79%
“…The Raman spectroscopic method was used to identify the molecular vibrational modes of BA-PI and PI (Figure S3). BA-PI has four main Raman modes with frequencies of 1185 cm –1 (C–C stretching of the perylene core and C–H in-plane bending), 1364 cm –1 (CH in-plane bending), 1458 cm –1 (CH wagging on the pyrene ring), 1575 cm –1 (CC/C–C stretching of the perylene core coupled with CH wagging), 1895 cm –1 (CO symmetric stretching of perylene core), and 646 cm –1 (C–N–C stretching of the imide group in polyimide). , PI exhibits similar Raman modes with frequencies of 1063 cm –1 (C–C stretching/C–H bending), 1300 cm –1 (C–H bending), 1367 cm –1 (C–H wagging on the aromatic ring), 1563 cm –1 (CC/C–C stretching), 1674 cm –1 (CO symmetric stretching of perylene ring), and 648 cm –1 (C–N–C stretching).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations